2020
DOI: 10.29408/edumatic.v4i2.2249
|View full text |Cite
|
Sign up to set email alerts
|

Tren Penggunaan Framework COBIT, ITIL, dan ISO 27001 Pada Rentang Tahun 2014-2018 di Indonesia

Abstract: The use of Information Technology (IT) frameworks from year to year in Indonesia has shown an increase. However, there is not much research on the use of IT frameworks. The research on IT frameworks can be used by a company to analyze trends in the use of frameworks in Indonesia. That way, it can help a company consider choosing a framework to use. The IT frameworks discussed in this study are COBIT, ITIL, and ISO 27001. Data related to research IT frameworks taken in the 2014-2018 period. Data collection thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Evaluasi terhadap tingkat kepabilitas organisasi dalam pengendalian keamanan informasi dapat mengacu ke beberapa kerangka kerja seperti misalnya ISO 27001, ITIL, atau COBIT [6]. Pada penelitian ini kerangka kerja yang digunakan adalah COBIT 2019 yang merupakan versi terbaru dari COBIT.…”
Section: Pendahuluanunclassified
“…Evaluasi terhadap tingkat kepabilitas organisasi dalam pengendalian keamanan informasi dapat mengacu ke beberapa kerangka kerja seperti misalnya ISO 27001, ITIL, atau COBIT [6]. Pada penelitian ini kerangka kerja yang digunakan adalah COBIT 2019 yang merupakan versi terbaru dari COBIT.…”
Section: Pendahuluanunclassified
“…The method used was descriptive quantitative. Based on published data from the Google Scholar database, results showed that the framework often used COBIT with a total of 523 articles [6]. However, the weakness of this research is the method used was unstandardized.…”
Section: Introductionmentioning
confidence: 98%
“…From a comparison of several search engines such as Google Scholar, Microsoft Academic, Scopus, and Web of Science, Google Scholar remains the most comprehensive publication source today [7]. Various publications can be obtained through Google Scholar, including scientific journals from various publishers [8]. Retrieval of data using Publish or Perish tools with the keyword Publisher, where Publisher is an Information System Journal which has been indexed by SINTA 2, 3, and 4.…”
Section: Introductionmentioning
confidence: 99%
“…Sesuai data Badan Pusat Statistik (2020), sebanyak 79,04 persen penduduk di Indonesia menggunakan internet untuk memperoleh berita/informasi. Hal ini didukung dengan adanya kemudahan akses internet sehingga peluang bagi siapapun untuk mencari informasi akan semakin luas (Rochmania, et al, 2020). Seiring dengan meningkatnya jumlah pengguna aktif internet, konsumsi terhadap program berita televisi streaming yang tersedia di situs juga meningkat (Andanni, 2021).…”
unclassified